PENGUBAHAN SIKAP SISWA SMA MUHAMMADIYAH BANGKINANG TERHADAP BAHAYA NARKOBA SEBAGAI EFEK SOSIALISASI - Rasyid, Anuar (SOROT, 2011)
The increase of dangerous drugs using cases, in Bangkinang affected the userdiscrete from the environment, family, society until country. The majority of dangerous drugsusers are adolescent in 11 until 19 years old. In the several time, a lot of adolescent useddangerous drugs because the minimum information that their gotten. There for, DWP, BNKand Polres Kampar held socialization in SMA Muhammadiyah Bangkinang to invite them foravoiding the drugs. The intention of this research is to know the socialization effect of thedangerous drugs to the student’s attitude of SMA Muhammadiyah Bangkinang.The researchdesign used kuantitative research by descriptive method. The account of sampel is 70people from 193 population. The sampel is decided from Quota Sampling technique, analyzemethod in this research used a formula P=F/N × 100%. The result of this research showsthat the socialization effect of dangerous drugs to the student’s attitude SMA MuhammadiyahBangkinang can be categoried good with the precentage is 95,09% and the socialization washeld by DWP, BNK and Polres Kampar to SMA Muhammadiyah Bangkinang was succesfull.